5 ( x + 2 ) ( x − 4 ) ( x + 1 ) ( x − 3 ) + 9 ( x + 4 ) ( x − 6 ) ( x + 3 ) ( x − 5 ) − 1 3 ( x + 6 ) ( x − 8 ) 2 ( x + 5 ) ( x − 7 ) = 5 8 5 9 2 .
If the real root of the above equation is of the form a ± b ,find a + b .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I thought I have a better way, but you are the best! :D
Log in to reply
Can you please show me your solution?
L e t t = x 2 − 2 x , a n d n = 8 . Then the equation after multiplying the factors is:- 5 ∗ ( t − n ) t − 3 + 9 ∗ ( t − 3 n ) t − 1 5 − 2 ∗ 1 3 ∗ ( t − 6 n ) t − 3 5 = 5 8 5 9 2 . ⟹ 5 ∗ ( t − n ) ( t − n ) + 5 + 9 ∗ ( t − 3 n ) ( t − 3 n ) + 9 − 2 ∗ 1 3 ∗ ( t − 6 n ) ( t − 6 n ) + 1 3 = 5 8 5 9 2 . ⟹ 5 1 + t − n 1 + 9 1 + t − 3 n 1 − 2 ∗ 5 1 − 2 ∗ t − 6 n 1 − 5 8 5 9 2 = 0 . B u t 5 1 + 9 1 − 1 3 2 − 5 8 5 9 2 = 0 . ∴ t − n 1 + t − 3 n 1 − t − 6 n 2 = 0 . ⟹ ( t − n ) ∗ ( t − 3 n ) ( t − 3 n ) + ( t − n ) − t − 6 n 2 = 0 B u t o n l y n u m e r a t o r = 0 , w i t h c o m m o n d e n o m i n a t o r . ⟹ ( 2 t − 4 n ) ∗ ( t − 6 n ) − 2 ∗ ( t − n ) ∗ ( t − 3 n ) = 0 ⟹ − 1 6 n t + 2 4 n 2 + 8 n t − 6 n 2 = 0 , n = 0 . ∴ − 8 t + 1 8 n = 0 , p u t t i n g v a l u e s o f t a n d n , W e g e t x 2 − 2 x − 1 8 = 0 , ∴ x = 1 ± 1 9 = a + b . a + b = 2 0
Problem Loading...
Note Loading...
Set Loading...
We have, 5 ( x + 2 ) ( x − 4 ) ( x + 1 ) ( x − 3 ) + 9 ( x + 4 ) ( x − 6 ) ( x + 3 ) ( x − 5 ) − 1 3 ( x + 6 ) ( x − 8 ) 2 ( x + 5 ) ( x − 7 ) = 5 8 5 9 2 .
Observing the numerators and denominators,we conclude that each of them contain the expression x 2 − 2 x ,so put ( x − 1 ) 2 = y ,our equation becomes 5 ( y − 9 ) y − 4 + 9 ( y − 2 5 ) y − 1 6 − 1 3 ( y − 4 9 ) 2 ( y − 3 6 ) = 5 8 5 9 2 . Now note that 5 1 + 9 1 − 1 3 2 = 5 8 5 9 2 .Subtracting corresponding terms we get,
5 ( y − 9 ) 5 + 9 ( y − 2 5 ) 9 − 1 3 ( y − 4 9 ) 2 ⋅ 1 3 = 0 ⟹ y − 9 1 + y − 2 5 1 − y − 4 9 2 = 0 ⟹ y − 9 1 − y − 4 9 1 = y − 4 9 1 − y − 2 5 1 ⟹ y − 9 − 4 0 = y − 2 5 2 4 ⟹ 3 ( y − 9 ) + 5 ( y − 2 5 ) = 0 ⟹ 8 y = 1 5 2 ∴ y = 1 9 ∴ x = 1 ± 1 9